Reflections on the topic of the angel of the home in Adelaida, a character in Fabla salvaje (1923) - Cordero San Martin, Gabriela Isabel (2023)
César Vallejo is one of the most representative figures of Peruvian literature and his works have been approached from different perspectives that have been debated until today. Thus, the novel Fabla salvaje, despite its short length, is a complex text that has been read mainly as a representation of identity conflict, dementia or masculinity. In view of this predominance, we consider that an approach to the female character in the novel is necessary in order to generate a reading that dialogues with other aesthetic proposals close to the work. In this sense, the present work will dialogue with the nineteenthcentury cliché of the «angel of the home», which is present in pictorial and literary art and which constitutes a stereotype of the role of women in society. The aim is to recognise the differences and similarities in the conformation of this cliché in Adelaide and Lucia, characters in Fabla salvaje and Aves sin nido, respectively.